Strategy To Manage Finance For Pertubuhan Masyarakat Indonesia (Permai) In Pulau Pinang Malaysia - Siswanti, Indra; Nawangsari, Lenny C.; Bin Rahmad, Khozaeni (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2024)
Indonesian citizen workers who are members of Pertubuhan Masyarakat Indonesia (PERMAI) in Pulau Pinang Malaysia, which is the object of this community service activity, needs to be equipped with an understanding of how to managing finance properly and correctly as well as how to evaluate financial management. In this way, it is hoped that the participants will be able to improve their standard of living and have sufficient savings for their future. For this reason, the Community Service team from Mercu Buana University Jakarta held Community Service activities. This activity will be carried out offline by making direct visits to Indonesian citizens who are members of the Pertubuhan Masyarakat Indonesia (PERMAI) in Pulau Pinang, Malaysia. Keywords: manage finance, evaluate financial management.